MODEL OF IMPLEMENTATION AND PICTURE OF COOPERATIVE TYPES OF PICTURES AND IMAGES TO IMPROVE CHILDREN'S LOGICAL AND SPEAKING THINKING ABILITY (Study on PAUD Children in Group B at Kindergarten Wahidah Ummatan Kepahiang) - Netti Herawati; Turdjai Turdjai (UNIB Press, 2018)
This study aims to improve the ability to think logically and speak to group B children at Kindergarten Ummatan Wahidah Kepahiang by applying a cooperative model type picture and picture. The type of research used is classroom action research. Classroom action research is carried out in 3 cycles, each cycle consists of four stages, namely: Planning, Implementation of Action, Observation, Reflection (reflection). The subjects of this study were children in group B which numbered 13 children. Data collection uses observation. On the results of the average value of logical thinking ability cycle 1 is obtained 1.98, becomes 2.48 in cycle 2 and increases in cycle 3 to 3.08. The speaking ability of cycle 1 was obtained at 2.37, becoming 2.59 in cycle 2 and increasing in cycle 3 to 3.04. This shows that the use of the cooperative model type picture and picture can improve the ability to think logically and speak to children in group B in the Kindergarten Ummatan Wahidah Kepahiang